Learning Ayurveda : the Guru-Shishya way - Dixit, M. R., (SAGE Knowledge. Cases., 2017)
The case presents an insight into the Guru Shishya Parampara. It is presents the outcome of a dialogue the case writers had with Rajvaidya Dhanshankarji G Pandit (Vaidyaji), a practitioner of Ayurveda system of medicine using Nadi Nidan - pulse diagnosis. The case presents Vaidyaji's family background, initial learning, and the admission process and describes the various stages of his learning and improvisation. It also explores the attributes of Guru and Shishya , acceptance of the Shishya by the Guru, processes of learning and evaluation, graduation, and revisit and renewal of learning.